KONSEP PAI WASATHIYYAH - Iwan Kurniawan. ZP (Pascasarjana s-3 IAIN Bengkulu, 2020)
In its history, Islam has provided many explanations to mankind about various concepts to live the right life in the world, and survive in the hereafter. Islamic Education has taught its adherents to behave wisely in all respects, and in every line of life, including those of moderate character, or also known as the word Wasathiyyah. In Islam, basically it covers all aspects, including this moderation aspect, so that Islam does not need additional words as Islam Wasathiyyah, because it is considered as a form of word wastage. With the characteristics of moderation, Islam has an important role to show the concept of Wasathiyyah to every adherent, as well as those who have beliefs outside of Islam. Moderation in religion has been exemplified in the Qur'an, Al Baqarah, verse 143, which in that verse, is described as Ummatan Wasathan. In the midst of the diverse conditions of trust in a pluralistic society, especially in Indonesia, a moderation in religion is very much needed, in order to create an atmosphere of harmony and conducive to the environment of the community itself. Islam has offered the concept, and now it needs the implementation of the values of the Wasathiyyah concept itself.